PEMBUATAN MATERIAL KOMPOSIT RESIN POLIESTER YANG DIPADUKAN LIMBAH KERTAS DAN ABU SEKAM PADI SEBAGAI PEREDAM AKUSTIK - Isran, Isran; Kadir, Abd; Hasanudin, La (Teknik Mesin Universitas Halu Oleo, 2018)
Noise pollution from noise is a kind of unwanted pollution.This noise can be reduced by using an acoustic damper. This study aims to find out the technique of making polyester resin material mixed with waste paperand rice husk ash as an acoustic damper. The composite made then tested the value of sound absorption coefficient (????), composite damping test is done on kundst tube impedance tool equipped with spekerr device, amplifer, power supllay, lettop, smartphone, oscilloscope, sound lever meter with input frequency 400,600,800 Hz. The composite making method used by determining the volume fraction in composite damping test of Noise Absorption Coefficient (NAC) properties comprising Resin polyster : 50% paper waste : 20% and rice husk ash: 30%, Resin polyster 50% paper waste: 30% and rice husk ash: 20%, Resin polyster : 50% paper waste: 40% and rice husk ash : 10%. The result of all polyester resin composite test specimens in paper waste and rice husk ash reinfercement have the highest absorption coefficient 0,47857????????) at fractoin of 50%:30%:20% volume with frequency of 800 Hz. While for the lowest sound absorption result 0,475819 (????) with volume fraction of 50%:30%:20% with frequency 400 Hz. The overall specimencan be made as a damper because it has a sound absorption coefficient value >0.3.Keyword: Composite, paper waste, rice husk ash and NAC